Small Mixed-Level Screening Designs with Orthogonal Quadratic Effects. Issue 4 (1st October 2016) - Nguyen, Nam-Ky; Pham, Tung-Dinh
Abstract : This paper discusses an algorithm for constructing mixed-level screening designs (MLSDs) by augmenting some columns of a definitive screening designs (DSDs) with additional two-level columns. The constructed designs have the quadratic effects being orthogonal to main effects. The algorithm is used to construct designs with the number of runs being equal to p (i.e., the number of model parameters) for even p or p + 1 for odd p. The performance of these small DSD-based MLSDs in terms of the D-efficiency is evaluated against the 60 small MLSDs of Yang et al. (2014).